Health Locus of Control With Diet Compliance In Diabetes Mellitus Patients - Sitti Fatimah Meylandri Arsad; Elvie Febriani Dungga; Rachmawaty D. Hunawa; Savina Cindi Kidamu (Universitas Negeri Gorontalo, 2023)
Diabetes mellitus (DM) is a chronic disease caused by the pancreas not being able to produce insulin effectively which is characterized by hyperglycemia. Blood sugar control can be done by adhering to the DM diet. Factors that influence adherence to diet include health locus of control (HLOC). The purpose of this study was to determine the relationship between HLOC and adherence to a diet in DM sufferers in the working area of the Telaga Health Center. This type of research is quantitative using the Cross Sectional approach method. The study population consisted of 194 DM sufferers in the working area of the Telaga Health Center. The number of samples was 66. The sampling technique was Simple Random Sampling. The results showed that 27 respondents (41%) had high HLOC, 39 respondents (59%) had moderate HLOC, and found no low HLOC (0%). Respondents with adherence to a good diet were 15 respondents (22.7%), adherence to an adequate diet were 48 respondents (72.7%) and adherence to a bad diet were 3 respondents (4.6%). Using the Somers'D test, a p-value = (0.000) is obtained so that there is a relationship between HLOC and adherence to diet in DM sufferers in the working area of the Telaga Health Center